2011
DOI: 10.1111/j.1600-6143.2010.03317.x
|View full text |Cite
|
Sign up to set email alerts
|

Selective Targeting of Human Alloresponsive CD8+ Effector Memory T Cells Based on CD2 Expression

Abstract: Costimulation blockade (CoB), specifically CD28/B7 inhibition with belatacept, is an emerging clinical replacement for calcineurin inhibitor-based immunosuppression in allotransplantation. However, there is accumulating evidence that belatacept incompletely controls alloreactive T cells that lose CD28 expression during terminal differentiation. We have recently shown that the CD2-specific fusion protein alefacept controls costimulation blockade-resistant allograft rejection in nonhuman primates. Here, we have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
149
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(159 citation statements)
references
References 59 publications
(75 reference statements)
8
149
1
1
Order By: Relevance
“…Multiple studies have established that early infiltration of CD8 + memory T cells into allografts, such as hearts, kidneys, and livers, facilitates accelerated rejection and presents a barrier to immunosuppression-mediated long-term graft survival (12,(15)(16)(17)(18)(19). Therefore, preclinical studies have focused on targeting this cell population in an effort to improve the survival of solid organ allografts, such as kidneys (17,20,21). However, some reports have indicated that CD8 + T cells with phenotypic and functional characteristics of memory cells can also downregulate immune responses.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have established that early infiltration of CD8 + memory T cells into allografts, such as hearts, kidneys, and livers, facilitates accelerated rejection and presents a barrier to immunosuppression-mediated long-term graft survival (12,(15)(16)(17)(18)(19). Therefore, preclinical studies have focused on targeting this cell population in an effort to improve the survival of solid organ allografts, such as kidneys (17,20,21). However, some reports have indicated that CD8 + T cells with phenotypic and functional characteristics of memory cells can also downregulate immune responses.…”
Section: Introductionmentioning
confidence: 99%
“…by our group and others (10)(11)(12)(13)(14)(15)(16). Belatacept is a first-in-class selective costimulation blocker and is clinically indicated as a CNI inhibitor substitute with mycophenolate mofetil and steroids after renal transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…A kostimuláció bénításán keresztül poszttranszplantációs immunszuppressziós alkalmazásának kipróbálása a fázis II klinikai kísérleteknél tart, ezek eredménye mostanában várható [9]. Főemlősökben végzett kísérletek során igazoló-dott, hogy az alefacept kiiktatja a memória-T-sejteket, CD28 és CD2 kombinált blokádjával teljes allog raft rejekció prevenciót tudtak elérni [23,24].…”
Section: Cd154-cd40 úTunclassified